2017
DOI: 10.1016/j.acthis.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caloric restriction on the forelimb skeletal muscle fibers of the hypertrophic myostatin null mice

Abstract: Skeletal muscle mass loss has a broad impact on body performance and physical activity. Muscle wasting occurs due to genetic mutation as in muscular dystrophy, age-related muscle loss (sarcopenia) as well as in chronic wasting disorders as in cancer cachexia. Food restriction reduces muscle mass underpinned by increased muscle protein break down. However the influence of dietary restriction on the morphometry and phenotype of forelimb muscles in a genetically modified myostatin null mice are not fully characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Although the deletion of myostatin results in an increase in the number of muscle fibers, as previously shown (McPherron & Lee, ; Elashry et al. , ), there was no alteration in fiber number after HFD for 10 weeks, which excludes not only the possibility of myofiber hyperplasia but also myofiber apoptosis/loss due to lipotoxicity. In agreement with our results, a study demonstrated that HFD intake for up to 16 weeks failed to induce autophagy or even apoptosis in soleus and plantaris muscles of rat (Campbell et al.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Although the deletion of myostatin results in an increase in the number of muscle fibers, as previously shown (McPherron & Lee, ; Elashry et al. , ), there was no alteration in fiber number after HFD for 10 weeks, which excludes not only the possibility of myofiber hyperplasia but also myofiber apoptosis/loss due to lipotoxicity. In agreement with our results, a study demonstrated that HFD intake for up to 16 weeks failed to induce autophagy or even apoptosis in soleus and plantaris muscles of rat (Campbell et al.…”
Section: Discussionsupporting
confidence: 65%
“…) as well as to atrophy after 5 weeks of dietary restriction (Elashry et al. ). The results suggest a compensatory mechanism to maximize energy utilization in the course of the HFD regimen by either reducing the size of the fast MHC fibers or by increasing the size of the slow fiber isoform.…”
Section: Discussionmentioning
confidence: 99%
“…This observation can be explained by a general decrease of the CSA regardless the different MyHC expressed. In this context, the CSA decrease was recently reported as an effect of a caloric restriction regimen (Elashry et al, 2017). It can be proposed that RES, as a caloric restriction mimetic, most probably reduces the CSA maintaining higher levels of MyHCIIB.…”
Section: Discussionmentioning
confidence: 90%